Measuring and comparing the level of athletic achievement for activities (fencing, weightlifting, table tennis) for the disabled challenge the impact of accidents and between the boy's disability challenge - Dr. Salim Najaf (physical education and sport sciences college for women/ Baghdad University, 2020)
The importance of the study stems from the inclusion of the handicapped in the sports community and the achievement of international accomplishments, and this requires knowing the preference between obstetric and handicap after accidents, which is the problem of scientific research from here highlights the importance of scientific research. As for the research objectives, the study of the percentages of achievements for a five-year period (2015-2020) for the players involved in International forums and tournaments from the Iraqi National Paralympic Committee, which represents the research sample and its human field. After the research procedures, the results were presented, analyzed and discussed, the following conclusions were reached that congenital handicap has a preference in achieving ratios of international and international achievements. Psychological, physical and social stability of childhood disability in good condition. The recommendations are the process of selecting players for childhood disability in activities (fencing, table tennis, weightlifting (Bing Press)). Rehabilitation of players from disability due to accidents, psychological rehabilitation before starting physical preparation